Opiate mediation of amenorrhoea in hyperprolactinaemia and in weight-loss related amenorrhoea. - Grossman, A; Moult, P; McIntyre, H; Evans, J; Silverstone, T; Rees, L; Besser, G (1982)
Endogenous opiates are involved in the control of pituitary gonadotrophin and PRL secretion, and possibly of food intake. Both hyperprolactinaemia and weight loss (especially in anorexia nervosa) are frequently associated with amenorrhoea and an absence of gonadotrophin pulsatility. Since it has been suggested that increased endogenous opiate tone may operate in both conditions, we infused high-doses of naloxone into twelve patients with amenorrhoea of whom five had hyperprolactinaemia and seven had weight-loss related amenorrhoea. Eleven of the twelve patients had low levels of oestradiol (less than 50 pmol/l). Naloxone induced a marked rise in both LH and FSH levels in all of the five hyperprolactinaemic patients. In contrast, the patients with weight-loss amenorrhoea responded to naloxone with only a small or no rise in gonadotrophins. There was no consistent change in PRL in either group of patients. It is concluded that in hyperprolactinaemia, but not weight-loss amenorrhoea, there is an important endogenous opiate-mediated tonic inhibition of secretion of hypothalamic gonadotrophin releasing hormone.